2022
DOI: 10.35848/1882-0786/ac6727
|View full text |Cite
|
Sign up to set email alerts
|

Study on silicidation reaction of Fe nanodots with SiH4

Abstract: We have demonstrated formation of Fe–silicide nanodots (NDs) on SiO2 by exposing Fe NDs to SiH4. The Fe NDs were formed by exposing ultrathin Fe film deposited on SiO2 to remote H2–plasma. After SiH4 exposure at 400°C, formation of Fe–silicide NDs with an areal dot density over 1011 cm−2 was confirmed. Photoluminescence from the Fe–silicide NDs was observable at room temperature in the near-infrared, being attributed to radiative recombination between quantized states in the NDs. The results will lead to the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
1
0
0
Order By: Relevance
“…From RT photoluminescence (PL) measurements, we have also found that the NDs after SiH 4 exposure at 400 °C show stable PL signals in the energy range from ∼0.7 to ∼0.85 eV associated with β-FeSi 2 ND formation. 27) In addition, we also confirmed that a distinct blue shift in PL spectra was clearly observed when the size of the Fe silicide NDs was decreased from ∼10.9 to ∼1.5 nm in average dot height by decreasing the initial Fe-film thickness. 28) Thus, the observed PL can be interpreted in terms of the radiative recombination of photogenerated carriers through quantized states of β-FeSi 2 NDs.…”
Section: Introductionsupporting
confidence: 76%
“…From RT photoluminescence (PL) measurements, we have also found that the NDs after SiH 4 exposure at 400 °C show stable PL signals in the energy range from ∼0.7 to ∼0.85 eV associated with β-FeSi 2 ND formation. 27) In addition, we also confirmed that a distinct blue shift in PL spectra was clearly observed when the size of the Fe silicide NDs was decreased from ∼10.9 to ∼1.5 nm in average dot height by decreasing the initial Fe-film thickness. 28) Thus, the observed PL can be interpreted in terms of the radiative recombination of photogenerated carriers through quantized states of β-FeSi 2 NDs.…”
Section: Introductionsupporting
confidence: 76%